Identification of plant taxons by isoelectric focusing - Stefanovits-Bányai, É.; Boross, L.; Bernáth, J.; Kerepesi, I.; Kiss, M.; Lakatos, S. (International Journal of Horticultural Science, 1999)
Differences were demonstrated in esterasei coenzyme pattern of some essential oil producing plants belonging to the Apiaceae family — fennel (Foeniculum vulgare Mill.), angelica (Angelica archangelica L.), lovage (Levisticum officinale Koch.), dill (Anethum graveolens L.), coriander (Coriandrum sativum L.), anise (Pimpinella anisum L.), caraway (Carum carvi L.) — as well as differences between two varieties of fennel seed by using isoelectric focusing. That method provides quality control in essential oil plants and is suitable to describe isoenzyme pattern characteristic for taxons. Based on our findings, isoelectric focusing seems to be suitable for identification and differentiation of different plant samples, providing an easy tool for further processing as well as for breeding. Our further aim is to apply that method to differentiate among samples belonging to the same species according to their value of inner content.